Deceptive Marketing - Firdaus, Humairah Fahima Hairanil; Abu Seman, Noor Aslinda; Harun, Amran (Penerbit UTHM, 2020)
Deceptive marketing is the use of inaccurate or false information to catch the attention of the user through the usage of misleading information to coax purchaser into a business transaction that will unusual be beneficial to the consumer but advantageous to the one that doing the deceptive advertising (Peter & Olson, 2010). Deceptive marketing has been marked in the literature which give an authority view about deception in marketing (Wilkins et al., 2016). Deceptive marketing is also a untrue claims or fake news about a firm’s products by competing firms can be understood in the context of misleading in marketing and unethical business practices and understanding the effects of unethical marketing is important, given that negative information is often more important to buyers than positive information and that firms can easily begin misleading marketing on the internet, especially through social media (Song et al., 2017). The requirement for a description of deceit in spreading is a long way from another concern (Ullah & Hussain, 2015). Overstatement of product quality is same as misleading facts about the product which it can be a structure of false praise. Whether and how much deceptive advertising impacts utilization is uncertain a reasoning because firms can counter-advertise to reveal deceptive assert by their opponents and consumers may be understood to ignore overstate declarations. Advertising in common and deceptive advertising in specific can be united, grow total utilization or ruthless, grow in demand share at the cost of opponents, or both.